2023
DOI: 10.1093/gbe/evad008
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning in Population Genetics

Abstract: Population genetics is transitioning into a data-driven discipline thanks to the availability of large-scale genomic data and the need to study increasingly complex evolutionary scenarios. With likelihood and Bayesian approaches becoming either intractable or computationally unfeasible, machine learning, and in particular deep learning, algorithms are emerging as popular techniques for population genetic inferences. These approaches rely on algorithms that learn non-linear relationships between the input data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 139 publications
(175 reference statements)
0
44
0
Order By: Relevance
“…Standard approaches to supervised machine learning rest on the assumption that the data they are used to analyze follow essentially the same distribution as the data used for training. In applications in population genetics, the training data are typically generated by simulation, leading to concerns about potential biases from simulation misspecification when supervised machine-learning methods are used in place of more traditional summary-statistic-or model-based methods (Caldas et al 2022;Korfmann et al 2023). In this article, we have shown that techniques from the "domain adaptation" literature can effectively be used to address this problem.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Standard approaches to supervised machine learning rest on the assumption that the data they are used to analyze follow essentially the same distribution as the data used for training. In applications in population genetics, the training data are typically generated by simulation, leading to concerns about potential biases from simulation misspecification when supervised machine-learning methods are used in place of more traditional summary-statistic-or model-based methods (Caldas et al 2022;Korfmann et al 2023). In this article, we have shown that techniques from the "domain adaptation" literature can effectively be used to address this problem.…”
Section: Discussionmentioning
confidence: 99%
“…This synthetic training data serves as the foundation of the new simulate-and-train paradigm of supervised machine learning for population genetics inference ( Fig. 1A, Schrider and Kern 2018; Korfmann et al 2023).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The task is generally framed as a classification problem, or sometimes a regression problem, where the network itself learns which aspects of the data are informative for the parameters in question. Since their introduction to the field, CNNs have been used to infer a variety of biological parameters and evolutionary processes, such as recombination rates, population sizes, migration rates and historical split times, as well as episodes of positive selection and adaptive introgression, to name a few (recently reviewed by Korfmann et al, 2023). Methods based on neural networks have produced very accurate results, as evaluated using simulations, where the ground truth is known.…”
Section: Introductionmentioning
confidence: 99%